Development of energy test procedure for household refrigerator-freezers in Malaysia - Saidur, Rahman; Nasrudin, A.R.; Masjuki, Haji Hassan; Choudhury, I.A.; Mahlia, T.M.I.; Husnawan, M. (International Journal of Power and Energy Systems, 2004)
Refrigerator-freezer energy consumption is greatly influenced by room temperature, thermostat setting positions, and door openings. To develop a realistic test procedure with respect to climatic conditions and usage patterns prevailing in a given country, the effect of these parameters on refrigerator-freezer energy consumption has to be taken into consideration. In order to do so, we have tested six household refrigerator-freezers of different capacities and brands in the laboratory. Using response surface methodology (RSM), we developed a mathematical model to co-relate energy consumption as a function of room temperature, thermostat setting positions, and door opening. Finally, modelled energy consumption was compared with the ISO specified standard energy consumption and field energy consumption to justify the possibilities of introducing ISO refrigerator-freezer energy test procedure in Malaysia. Based on the above comparison, we observed that ISO test standards can be adopted for testing and rating of these appliances in Malaysia.